„Arena für alle“ – zur schwedischen Bibliotheksdebatte - Wischmann, Antje (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2022)
The Swedish Library Act which was adopted in 2014 has been an important reference point until today for the continuous debate on the public mandate of libraries and on how libraries contribute to promoting democracy. Based on this act, the practical work of libraries is expressed and reflected in the library plans of municipalities or individual libraries. The plans and reports from the years 2016 to 2021 bear witness to the challenges posed by the widening social divide and the transformation of the public sphere through the media. The agendas of libraries are currently undergoing a process of politicisation which could affect how library staff see themselves and what is taught in library and information science.
Keywords: Library policy; Swedish library law; Library debate; Library staff; Institutional neutrality; Arena